Giant Hepatic Hemangioma Regressed Significantly Without Surgical Management: A Case Report and Literature Review - Zhang, Jingcong; Ye, Zuyang; Tan, Lei; Luo, Jinmei (Frontiers in Medicine, 2021)
Hepatic hemangioma (HH) is a congenital vascular anomaly comprising networks of abnormal blood and/or lymphatic vessels with endothelial cell proliferation. Their pathophysiology is not fully understood, and no specific drug is available to treat them. Conservative management, which limits observation, is preferred for most patients. A HH larger than 4 cm is considered a giant HH that may be treated using surgery ranging from embolization to hepatic resection or liver transplantation. Here, we describe a case with multiple and giant HHs that regressed significantly after treatment with azithromycin (AZM). A systematic literature review of HH and the effects of AZM on angiogenesis was then conducted.